Initial testing (stage 1) of the investigational mTOR kinase inhibitor MLN0128 by the pediatric preclinical testing program. Issue 8 (20th February 2014) - Kang, Min H.; Reynolds, C. Patrick; Maris, John M.; Gorlick, Richard; Kolb, E. Anders; Lock, Richard; Carol, Hernan; Keir, Stephen T.; Wu, Jianrong; Lyalin, Dmitry; Kurmasheva, Raushan T.; Houghton, Peter J.; et al.
Abstract MLN0128 is an investigational small molecule ATP‐competitive inhibitor of the serine/threonine kinase mTOR. MLN0128 was tested against the in vitro panel at concentrations ranging from 0.1 nM to 1 μM and against the PPTP in vivo panels at a dose of 1 mg/kg administered orally daily × 28. In vitro the median relative IC50 concentration was 19 nM. In vivo MLN0128 induced significant differences in EFS in 24/31 (77%) solid tumor models, but 0/7 ALL xenografts. The modest activity observed for MLN0128 against the PPTP preclinical models is similar to that previously reported for another TOR kinase inhibitor. Pediatr Blood Cancer 2014; 61:1486–1489. © 2014 Wiley Periodicals, Inc.